If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(4 + -6x) + 5(13y + 1) = 9 (4 * 11 + -6x * 11) + 5(13y + 1) = 9 (44 + -66x) + 5(13y + 1) = 9 Reorder the terms: 44 + -66x + 5(1 + 13y) = 9 44 + -66x + (1 * 5 + 13y * 5) = 9 44 + -66x + (5 + 65y) = 9 Reorder the terms: 44 + 5 + -66x + 65y = 9 Combine like terms: 44 + 5 = 49 49 + -66x + 65y = 9 Solving 49 + -66x + 65y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -66x + -49 + 65y = 9 + -49 Reorder the terms: 49 + -49 + -66x + 65y = 9 + -49 Combine like terms: 49 + -49 = 0 0 + -66x + 65y = 9 + -49 -66x + 65y = 9 + -49 Combine like terms: 9 + -49 = -40 -66x + 65y = -40 Add '-65y' to each side of the equation. -66x + 65y + -65y = -40 + -65y Combine like terms: 65y + -65y = 0 -66x + 0 = -40 + -65y -66x = -40 + -65y Divide each side by '-66'. x = 0.6060606061 + 0.9848484848y Simplifying x = 0.6060606061 + 0.9848484848y
| 3x+7-5x= | | 4k-14+3/c=21 | | 5h=2 | | 0=2m-18 | | -0.3f+1.3=4.8 | | -18/y+3 | | (x+16)+(x+22)=231 | | y^2-3y/y+3 | | 5(4x)-1/2x=234 | | 9h+4.5-7h+1.75= | | 6x+3x-3= | | 12+7C=103 | | 21-1y=-87+2y | | 6y-5-2y=-31 | | -2/3n-6=18 | | -7+28m=13(2m-3) | | 2v-54=-1v+21 | | 0.5n+0.3n-0.4n= | | 2x=14+2 | | 12-7y=40 | | 12x+y-x+6y= | | 7x-2x+2-x= | | 6n+10=-44 | | 2/3k=4/3 | | 4x^2+176=0 | | 8p-9=49 | | 2x^2+19+24=0 | | 2x/7-2x=x/2+17/2 | | 12/3+4-24/3x8 | | 5+(2-x)/3=7 | | K/4+5=4 | | 4x-9x=45 |